A conceptual model for glaciogenic reservoirs: From landsystems to reservoir architecture. (May 2020) - Kurjanski, Bartosz; Rea, Brice R.; Spagnolo, Matteo; Cornwell, David G.; Howell, John; Archer, Stuart
Abstract: Glaciogenic sediments are present in many hydrocarbon-producing basins across the globe but their complex nature makes it difficult to characterise the reservoir-quality sedimentary units. Despite this, Ordovician glacial deposits in North Africa, and Carboniferous-Permian glaciogenic sequences in the Middle East, have been proven to host significant, economical, hydrocarbon accumulations. Additionally, discoveries have been made in the shallow (<1000 m below seabed), glacial, Pleistocene sedimentary succession of the North Sea (e.g. Peon and Aviat). This paper provides a predictive exploration framework in the form of a conceptual model of glaciogenic sediment-landform distributions. The model is based on the extensive onshore glacial sedimentary record integrated with available offshore data. It synthesises the published knowledge, drawing heavily on glacial landsystem models, glacial geomorphology and sedimentology of glaciogenic deposits to provide a novel conceptual model allowing for the efficient description and interpretation of glacial sediments and landforms in the subsurface. Subsequently, land-terminating and water-terminating ice sheet depositional systems are described and discussed, with respect to ice advance and retreat cycles. This detailed description focuses on the macro-scale stratigraphic organisation of glacial sediments with relation to the ice margin, aiding the prediction of glaciogenic sediment distributions, and their likely geometry, architecture and connectivity as reservoirs. Highlights: A novel conceptual model for the distribution of glaciogenic reservoirs. First-pass interpretation tool for complex glaciogenic sequences. Ice margin position controlling reservoir quality. Identification of landforms and sediments crucial to reservoir predictability.